Analisis Yuridis Kebocoran Data di Layanan Kesehatan Digital: Studi Kasus Aplikasi Telemedicine di Indonesia - Nadiroh, Aenun; Wiraguna, Sidi Ahyar (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of telemedicine services in Indonesia has become an innovative solution in providing remote healthcare access, particularly since the COVID-19 pandemic. However, behind this progress lies a serious legal issue regarding the leakage of patients’ personal data, which remains inadequately addressed. This study aims to analyze the legal aspects of personal data protection in telemedicine services using a normative legal approach, focusing on statutory regulations such as Law No. 27 of 2022 on Personal Data Protection and related health sector policies. The findings indicate that, despite the presence of a formal legal framework, practical implementation remains weak, as evidenced by multiple data breach incidents, including the e-HAC and COVID-19 patient medical record cases. Existing technical regulations fall short in addressing the complexity of digital systems, while awareness among service providers regarding privacy and accountability principles remains insufficient. Therefore, the protection of patient data must be seen as an integral part of digital medical services through effective legal enforcement and the strengthening of ethical and transparent data governance.